The antioxidant activity and stability of yogurt fortified with rosella (Hibiscus sabdariffa Linn) calyx extract - Nurkhasanah Mahfudh; Amraini Amelia (Universitas Ahmad Dahlan, 2020)
Roselle calyx Â (Hibiscus sabdariffa Linn) contains many anthocyanins. The purpose of this study was to determine the anthocyanin stability and antioxidant activity of rosella calyx extract and rosella calyx fortified in yogurt. Roselle calyx extract (Hibiscus sabdariffa Linn) was obtained by the infundation method using water at 90 Â° C for 15 minutes. Rosella calyx extract was made into yogurt with a concentration of 0%, 2%, 4% and 8%, full cream liquid milk 13% (100 ml), and a 5% bacterial starter combination concentration (1: 1 b/v). The yogurt evaluation included a stability test with storage at 4Â°C and antioxidant activity using the DPPH method on 0, 7, 14, 21, and 28 days. The data was statistically analyzed using Multivariate Analysis of Variance (MANOVA). The anthocyanin stability of the three samples, namely roselle extracts of 2%, 4%, and 8%, significantly different (p <0.05) for each concentration of roselle calyx extract and the antioxidant activity of roselle calyx yogurt in the three samples 2% 4% and 8% were significantly different for each concentration of rosella calyx extract added to yogurt. During storage, anthocyanin stability and antioxidant activity of rosella calyx yogurt extract on day 0 to 7 did not differ significantly, while 14 to 28 were significantly different. The 4% and 8% concentrations of rosella calyx yogurt produce optimal yogurt formula